Evolution and biogeography of Anablepsoides killifishes shaped by Neotropical geological events (Cyprinodontiformes, Aplocheilidae). (12th April 2022) - Amorim, Pedro F.; Costa, Wilson J. E. M.
Abstract: Anablepsoides is a widely distributed Neotropical killifish genus found in shallow streams, in both dense forests and open areas, throughout northern and northeastern South America. The phylogenetic and biogeographic relationships of the genus are here analysed, based on two nuclear and four mitochondrial genes of 26 species and six out‐groups. The origin of Anablepsoides was recovered in Early Miocene in an area corresponding to the Paleo‐Amazon‐Orinoco system. The current analyses indicate that the initial diversification of the genus in two main clades was associated with marine transgressions related to the formation of the Pebas mega‐wetland isolating each MRCA of those main clades in the upper Amazon river basin and river basins of the Guiana Shield. The diversification of the genus and the colonisation of new areas may be associated with Miocene and Pliocene events such as changes in the sea level, formation and extinction of wetlands, rupture of the Purus arch and Amazon river assuming the current flow to the East. Also, the evolution of Anablepsoides could be associated with the diversification of several other Neotropical lineages, so that the present study leads to a better understanding of the evolution of the Neotropical freshwater biota and South American geological history.